Quality of life and vocal health of teachers - Penteado, Regina Zanella; Pereira, Isabel Maria Teixeira Bicudo (Revista de Saúde Pública, 2007)
OBJECTIVE: To evaluate aspects of teachers' quality of life and describe associated factors to their vocal health. METHODS: A sample comprising 128 high school teachers from four state schools in the city of Rio Claro, Southeastern Brazil, was studied in 2002. The World Health Organization Quality of Life/bref and Voice-Related Quality of Life questionnaires were applied and there were calculated the averages, standard deviation values for the first questionnaire scores and the self-evaluation question of the Voice-Related Quality of Life. The Wilcoxon's test was used to compare teachers' genders; the Kruskal-Wallis's test was used to compare schools and Spearman's correlation coefficient and t-test were performed to assess the association between the domains of quality of life, the vocal self-evaluation question and age, and the number of working shifts by a teacher. RESULTS: Most teachers evaluated their voice as good (42.2%) and the mean score of the quality of life questionnaire was 66, with the highest scores in the domain of social relations, and the lowest ones in the environment domain. The most affected aspects were leisure opportunities, financial conditions, work environment and access to information. The number of hours worked by a teacher had a positive significant correlation with vocal self-evaluation. There were no significant differences between genders. There were significant differences in the physical domain when comparing schools. CONCLUSIONS: Although teachers showed to be reasonably satisfied with their vocal and life quality, they showed misperceptions of their health disorder process and evidenced neglected aspects of life quality and health needs that may compromise teachers' voice/vocal health.